2003
DOI: 10.1007/s00238-002-0453-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of intense pulsed light in the treatment of scars

Abstract: Skin healing results in scar formation, which can be atrophic, proliferative, erythematous, or pigmented. Many different procedures are available for improving scars: surgical, topical medications, local irradiation, cryosurgery, and ablative or nonablative lasers. Intense pulsed light sources emit noncoherent, broadband wavelength, pulsed light that can treat vascular and pigmented lesions and therefore act on the vasculature and the pigmentation of a scar to improve its appearance and/or symptoms that may co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 8 publications
3
28
3
Order By: Relevance
“…It was shown that improvement level in most patients was more than 75% and a decrease of more than 50% was observed in lesion size. This study matches the findings of the present study (9). In a study by Erol et al…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…It was shown that improvement level in most patients was more than 75% and a decrease of more than 50% was observed in lesion size. This study matches the findings of the present study (9). In a study by Erol et al…”
Section: Discussionsupporting
confidence: 94%
“…In our study, however, no case of purpura was observed (1). In another study (Kontoes et al), blister and crust were observed following treatment with IPL plus injection, while no such complications were observed in our study (9). In a study carried out by Manuskiatti et al in 2002, complications of corticosteroid intralesional injection included hypopigmentation, atrophy and telangiectasia in 50% of treated lesions (19).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations